2020
DOI: 10.1007/s10719-020-09964-6
|View full text |Cite
|
Sign up to set email alerts
|

Metal cations promote α-dicarbonyl formation in glucose-containing peritoneal dialysis fluids

Abstract: Heat sterilization of peritoneal dialysis fluids (PDFs) leads to the formation of glucose degradation products (GDPs), which impair long-term peritoneal dialysis. The current study investigated the effects of metal ions, which occur as trace impurities in the fluids, on the formation of six major α-dicarbonyl GDPs, namely glucosone, glyoxal, methylglyoxal, 3-deoxyglucosone, 3-deoxygalactosone, and 3,4-dideoxyglucosone-3-ene. The chelation of metal ions by 2-[bis[2-[bis(carboxymethyl)amino]ethyl]amino]acetic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Glucosone is formed by the oxidation of glucose 20 , 21 . Recently, it was shown that traces of redox-active metal ions, such as iron(II), can promote the formation of the oxidized GDP glucosone and, to a lesser extent, also glyoxal and MGO 22 . The concentrations of 3-DG, 3-DGal, and 3,4-DGE, which are formed by non-oxidative mechanisms 2 were not affected by metal ions 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucosone is formed by the oxidation of glucose 20 , 21 . Recently, it was shown that traces of redox-active metal ions, such as iron(II), can promote the formation of the oxidized GDP glucosone and, to a lesser extent, also glyoxal and MGO 22 . The concentrations of 3-DG, 3-DGal, and 3,4-DGE, which are formed by non-oxidative mechanisms 2 were not affected by metal ions 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that traces of redox-active metal ions, such as iron(II), can promote the formation of the oxidized GDP glucosone and, to a lesser extent, also glyoxal and MGO 22 . The concentrations of 3-DG, 3-DGal, and 3,4-DGE, which are formed by non-oxidative mechanisms 2 were not affected by metal ions 22 . Thus, traces of metal ions from raw materials or production equipment may be responsible for the formation of glucosone during the storage of double-chamber PDFs.…”
Section: Discussionmentioning
confidence: 99%